2002
DOI: 10.1139/a02-007
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of North American boreal mixedwoods

Abstract: Boreal mixedwoods (BMWs) are the most productive and diverse forest ecosystems in North American boreal forests. A good understanding of BMW stand dynamics is a prerequisite for sustainable management of these vital resources. In this review, we describe the patterns and processes of BMWs created by natural disturbances, examine the biotic and abiotic factors that influence these patterns and processes, and discuss forest management implications related to stand development. Based on distinct structural and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
309
1
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 334 publications
(334 citation statements)
references
References 106 publications
13
309
1
1
Order By: Relevance
“…Following the growth influx, a decrease in tree loads [34,73] was predicted at 80, 110, and 200 years for TA, JP, and BS forests, respectively. Over time, tree mortality starts, gaps are created, and shade-tolerant species appear in the canopy [74,75]. Our predictions concur with previous observations: Pothier et al [76] estimated tree productivity loss after about 60 years for TA forest in Quebec; Belleau et al [50] estimated composition changes to occur in the Clay Belt region at around 70 to 120 years for JP and TA forests, respectively, and at around 100 to 200 years for BS forests.…”
Section: Fuel Load Dynamics With Tsfsupporting
confidence: 89%
“…Following the growth influx, a decrease in tree loads [34,73] was predicted at 80, 110, and 200 years for TA, JP, and BS forests, respectively. Over time, tree mortality starts, gaps are created, and shade-tolerant species appear in the canopy [74,75]. Our predictions concur with previous observations: Pothier et al [76] estimated tree productivity loss after about 60 years for TA forest in Quebec; Belleau et al [50] estimated composition changes to occur in the Clay Belt region at around 70 to 120 years for JP and TA forests, respectively, and at around 100 to 200 years for BS forests.…”
Section: Fuel Load Dynamics With Tsfsupporting
confidence: 89%
“…For instance, sapling radial growth data from our study area indicate that aspen starts to outgrow white spruce and balsam fir above ∼50% GLI (Poulin and Messier, 2006). Chen and Popadiouk (2002) suggested that light levels higher than 40% are required for aspen establishment and Bourgeois et al (2004) concluded that a ∼60% removal rate, through a uniform harvest pattern, could contribute to accelerate the transition from aspen toward mixedwood stands.…”
Section: Management Implicationsmentioning
confidence: 99%
“…and white spruce (Picea glauca (Moench) Voss), are a prominent component of the boreal forest in Western Canada [1,2]. Mixedwood forests represent a range of early-to mid-seral successional stages [3] and develop most commonly on mesic and subhygric sites [4,5] where successional pathways are more variable than on dry or wet sites [6]. When aspen and white spruce regenerate at approximately the same time following disturbance, aspen will form an overstorey above spruce for at least 50-60 years.…”
Section: Introductionmentioning
confidence: 99%